2016
DOI: 10.2147/cia.s116430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of whole body electromyostimulation on cardiometabolic risk factors in older women with sarcopenic obesity: the randomized controlled FORMOsA-sarcopenic obesity study

Abstract: BackgroundSarcopenic obesity (SO) is characterized by a combination of low muscle and high fat mass with an additive negative effect of both conditions on cardiometabolic risk. The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on the metabolic syndrome (MetS) in community-dwelling women aged ≥70 years with SO.MethodsThe study was conducted in an ambulatory university setting. Seventy-five community-dwelling women aged ≥70 years with SO living in Northern Bavaria, Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 42 publications
6
77
2
1
Order By: Relevance
“…Whole‐body electromyostimulation training is able to stimulate all the main muscle groups with dedicated intensity simultaneously and has become increasingly popular during the last decade. A total of 21 studies have investigated its influence on physical fitness and health in trained and untrained individuals, and in patients who cannot perform conventional modalities of exercise because of physical or mental illness . Most of these studies (n = 10) have examined the role of whole‐body electromyostimulation training on body composition parameters, showing that this training modality induced a generally decrease of FM and a generally increase of LM in (a) sedentary older men and women with sarcopenic obesity (all of them aged > 70 years old), (b) in sedentary older women with obesity (aged > 70 years old), (c) in moderately trained male runners, (d) in sedentary healthy men (aged 30‐50 years old), and (e) in moderately trained healthy women (aged > 55 years old) .…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐body electromyostimulation training is able to stimulate all the main muscle groups with dedicated intensity simultaneously and has become increasingly popular during the last decade. A total of 21 studies have investigated its influence on physical fitness and health in trained and untrained individuals, and in patients who cannot perform conventional modalities of exercise because of physical or mental illness . Most of these studies (n = 10) have examined the role of whole‐body electromyostimulation training on body composition parameters, showing that this training modality induced a generally decrease of FM and a generally increase of LM in (a) sedentary older men and women with sarcopenic obesity (all of them aged > 70 years old), (b) in sedentary older women with obesity (aged > 70 years old), (c) in moderately trained male runners, (d) in sedentary healthy men (aged 30‐50 years old), and (e) in moderately trained healthy women (aged > 55 years old) .…”
Section: Introductionmentioning
confidence: 99%
“…The lipid profile is the most studied risk factor, being present in eleven articles. Of these, eight were performed in Asian elderly individuals [7,9,10,16,17,22,23,24] and only three in non-Asian individuals (the USA, Germany and Brazil) [12,25,26]. However, none of the studies analyzed the lipid profile as their main objective, which limits the conclusions about their results.…”
Section: Sarcopenic Obesity and Risk Factors For Cardiometabolic And mentioning
confidence: 99%
“…However, none of the studies analyzed the lipid profile as their main objective, which limits the conclusions about their results. Changes in the lipid profile were characterized by high levels of total cholesterol [24], triglycerides [10,17,23,24] and reduced high-density lipoprotein [10,17,[23][24][25]. Studies evaluating the lipid profile of the elderly used the following diagnostic criteria for sarcopenia: the cross-sectional area of the quadriceps muscle adjusted by the Body Mass (BM) through a CT and a height-adjusted MM, and the BM assessed through a DXA and a BIA.…”
Section: Sarcopenic Obesity and Risk Factors For Cardiometabolic And mentioning
confidence: 99%
See 1 more Smart Citation
“…WB-EMS stimulates all main muscle groups simultaneously during a moderate exercise and can be considered as a time-efficient option to high-intensity resistance exercise improving the general strength (Wolfgang . Furthermore, WB-EMS affects positively the body composition and fitness parameters by enhancing the energy expenditure and by improving the isometric strength (Boccia et al, 2017;Maggioni et al, 2010), and it has been observed to be an effective method for cardio-metabolic risk factors prevention in previous studies (Wolfgang Kemmler, Kohl, Freiberger, Sieber, & von Stengel, 2018;Wittmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%